Screening of Five Lactobacillus Bacteria with Probiotic Properties from Indigenous Klila Cheese - Saci, Ahmed; Gharbi, Samia; Djadouni, Fatima; Karkachi, Noureddine (The North African Journal of Food and Nutrition Research, 2025)
Background: The Lactobacillus genus is the most widespread lactic acid bacteria (LAB) species globally. These bacteria are known for their probiotic properties, which benefit human health. Aims: This study aims to identify and screen the principal probiotic selection criteria of five Lactobacillus strains isolated from Klila, a traditionally fermented cheese product from Algeria, in vitro.Materials and Methods: The main probiotic selection criteria were screened in vitro through biochemical and physiological tests, such as tolerance to low pH, bile salts, and phenol, their aggregation capacity, cell surface hydrophobicity, antibiotic sensitivity, and antimicrobial activity. Sequencing the 16S-rRNA gene identified the five isolates as Lactobacillus plantarum (LP1, LP2, LP3, and LP4) and Lactobacillus fermentum (LF1).Results: The experimental results showed that all five isolates survived after exposure to low pH (2.2) for 3 hours. They also showed tolerance to bile salts ranging from 57.67 to 70.68% and 0.4% phenol, ranging from 39.22 to 61.01%. The auto-aggregation capacity varied between 31.35% and 57.38%, while co-aggregation varied respectively from 14.57% to 22.17% with Escherichia coli, from 13.04% to 23.62% with Staphylococcus aureus, and from 11.15% to 17.03% with Candida albicans. The hydrophobicity towards xylene ranged from 41.67 to 60.47%, and the biofilm formation ability ranged from 32.94 to 70.19%. Isolate LF1 presented the highest hydrophobicity and biofilm formation percentages, with 60.47 and 70.19%, respectively. All five isolates demonstrated significant antioxidant capacities, suggesting their potential to improve food preservation and health benefits. Exceptional antimicrobial activities were revealed against the tested food-borne pathogens, ranging from 12.6 to 45 mm. A safety profile was shown without hemolytic, gelatin liquefaction, or coagulase activity.Conclusion: The Lactobacillus bacteria isolated from Klila presented physiological characteristics that make them potential probiotic candidates beneficial for health.Keywords: Lactobacillus; Lactic Acid Bacteria; Probiotic Potential; Antimicrobial Activity; Traditional Algerian Cheese.
Keywords: Lactobacillus; Lactic acid bacteria; Probiotic potential; Antimicrobial activity; Traditional Algerian Cheese